2009
DOI: 10.1051/0004-6361/200912119
|View full text |Cite
|
Sign up to set email alerts
|

Non-circular motions and the cusp-core discrepancy in dwarf galaxies

Abstract: Context. The cusp-core discrepancy is one of the major problems in astrophysics. It results from comparing the observed mass distribution of galaxies with the predictions of cold dark matter simulations. The latter predict a cuspy density profile in the inner parts of galaxies, whereas observations of dwarf and low surface brightness galaxies show a constant-density core. Aims. We want to determine the shape of the dark matter potential in the nuclear regions of a sample of six nearby irregular dwarf galaxies.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 61 publications
5
38
1
Order By: Relevance
“…This is consistent with results previously found in other nearby dwarf and LSB galaxies (e.g., de Blok & Bosma 2002;Kuzio de Naray et al 2008;van Eymeren et al 2009;Oh et al 2011b). The slowly increasing DM rotation curves in the inner region of the sample galaxies reflect a halo whose gravitational potential is not deep enough to sustain the power-law DM density cusps that are as steep as ρ ∝ − R 1.0 .…”
Section: Core-like Halo Modelsupporting
confidence: 93%
“…This is consistent with results previously found in other nearby dwarf and LSB galaxies (e.g., de Blok & Bosma 2002;Kuzio de Naray et al 2008;van Eymeren et al 2009;Oh et al 2011b). The slowly increasing DM rotation curves in the inner region of the sample galaxies reflect a halo whose gravitational potential is not deep enough to sustain the power-law DM density cusps that are as steep as ρ ∝ − R 1.0 .…”
Section: Core-like Halo Modelsupporting
confidence: 93%
“…The sample consists of 211 galaxies of different types. We used the following approaches to the DM parameter estimation described in Section 2: (i) -best fit modelling of the rotation curves (Shchelkanova et al 2013, Barnes et al 2004, Kasparova 2012, Chemin et al 2006, van Eymeren et al 2009, Weijmans et al 2008, Spano et al 2008 (iv) -approach based on the spectral energy distribution and longslit spectra modelling (Kasparova et al 2014); (v) -method relying on the marginal gravitational stability of the disc (Shchelkanova et al 2013, Saburova & Zasov 2012); (vi) -approach taking into account the presence of spiral structure (Athanassoula et al 1987); (vii) -method in which the stellar mass-to-light ratio is obtained from the colour index (the so-called "Bottema disc" of de Blok & McGaugh 1997); (viii) -method based on the X-ray properties of hot gas (Humphrey et al 2006); (ix) -Jeans analysis based on planetary nebulae or stellar kinematical data (Napolitano et al 2009, Napolitano et al 2011, Weijmans et al 2009, Frigerio Martins 2009; (x) -modelling reproducing the observed velocity dispersion profiles and number density profiles (Wu 2007). …”
Section: Resultsmentioning
confidence: 99%
“…Astronomical observations show that the DM galaxy density profiles are cored till scales below the kpc [20][21][22][23][24][25]. On the other hand, N -body CDM simulations exhibit cusped density profiles with a typical 1/r behavior near the galaxy center r = 0.…”
Section: Introductionmentioning
confidence: 99%